2013
DOI: 10.1186/1471-2342-13-1
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal image registration of the scoliotic torso for surgical planning

Abstract: BackgroundThis paper presents a method that registers MRIs acquired in prone position, with surface topography (TP) and X-ray reconstructions acquired in standing position, in order to obtain a 3D representation of a human torso incorporating the external surface, bone structures, and soft tissues.MethodsTP and X-ray data are registered using landmarks. Bone structures are used to register each MRI slice using an articulated model, and the soft tissue is confined to the volume delimited by the trunk and bone s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…X-ray and TP data using articulated models and constrained thin-plate splines. 3 The articulated model represents the spine as a series of rigid, local, inter-vertebral transformations. First, a local coordinate system is obtained for each of the lumbar and thoracic vertebrae in each of the MRI and X-ray modalities using the manually obtained vertebral landmarks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray and TP data using articulated models and constrained thin-plate splines. 3 The articulated model represents the spine as a series of rigid, local, inter-vertebral transformations. First, a local coordinate system is obtained for each of the lumbar and thoracic vertebrae in each of the MRI and X-ray modalities using the manually obtained vertebral landmarks.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously obtained a full model of the patient's torso that incorporates bone structures, soft tissues and the external surface of the torso. 3 However, inter-patient registration was not performed. Most previous inter-patient registration methods focused on the brain.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the number of points is too large, the computation time may be too long for the optimization. Moreover, to our best knowledge, the registration of vertebrae was treated as a rigid registration problem in the literature [15] [16], and thus we prefer a rigid registration method rather than a non-rigid registration one. In this paper, we adopt the Fourier moment matching method [2], which is based on the fact that the affine transform between two point sets corresponds to a related affine transform between their Fourier spectrums, and the moments for the corresponding Fourier spectrum distributions can be calculated as probability density function.…”
Section: A Point Set Registrationmentioning
confidence: 99%
“…It was shown that a completely rigid or completely elastic transformation was not able to compensate for the difference in posture between the two modality acquisitions. Finally, the soft tissue provided by the MR images was confined to the volume delimited by the trunk and bone surfaces using a constrained Thin-Plate Splines method [34]. Figure 4a shows a clear misalignment between the vertebrae extracted from X-ray data and those extracted from MRI data when rigid registration is used.…”
Section: Multimodal Image Fusionmentioning
confidence: 99%